Monitoring System Kecepatan dan Arah Angin Berbasis Internet of Things (IoT) Menggunakan Raspberry Pi 3 - Fernando, Makmur; Jasa, Lie; Hartati, Rukmi Sari (Majalah Ilmiah Teknologi Elektro, 2022)
Wind is a natural resource that has many benefits for human life, for example, wind can be used to generate electricity, namely the wind power plant, for aircraft navigation purposes during takeoff and landing, as well as for aerospace sports such as paragliding, parasailing and aeromodeling. The existence of wind can also be detrimental to mankind, such as the existence of extreme weather that allows hurricanes, rainstorms, floods and landslides and high sea waves. This study expects to design a prototype tool monitoring system for wind speed and wind vane based on the Internet of Things (IoT) using the Raspberry Pi 3 model B+ as a data processor that can give data abouttwind speed and direction of the wind in realtime and can be accessed remotely when connected to the internet network. Test data read from the sensors displayed on the LCD 16 x 2 and sent to the web server using a router with the goal that it tends to be monitored online by the user with an internet connection. Wind speed data is read in rotations per minute (rpm) and wind direction data can detect up to 16 wind directions. The conclusion of this study is that the based wind speed and wind direction monitoring system Internet of Things (IoT) using Raspberry Pi 3 Model B+ can work properly. Wind speed and wind course information are stored in a database, which can be accessed on web the Telegram in realtime. Data transmission of wind speed and wind directions takes place every 1 minute.